GAMBARAN TINGKAT STRES KERJA PERAWAT DI RUANG ISOLASI COVID-19 RSUD BALI MANDARA - Kadek Lia Ari Pramadewi; Komang Menik Sri Krisnawati; Kadek Eka Swedarma (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
Work stress is an emotional condition caused by workload and individual’s ability to cope their job demands. Nurses’ work stress during COVID-19 pandemic may occur due to high workload, dealing with patients’ death and dying, personal demands and fears, personal protection equipment usage, stigma, and risk of infection. The purpose of this study was to determine the description of the work stress level of nurses in COVID-19 isolation department of Bali Mandara hospital. This research was a descriptive quantitative study using total sampling technique. Samples in this study were 74 respondents. The results showed that the majority of nurses had an age range 26-35 years old (77,0%), female (66,2%), nursing diplome degree (52,7%), and nursing working experience <3 years (64,9%). Nurses’ work stress level were dominantly at mild work stress level (56,8%) and moderate work stress level (43,2%). The majority nurses who have moderate work stress level are 26-35 years old (81,3%), female (62,5%), bachelor degree/Ners (53,1%), and nursing working experience <3 years (68,8%).